Countries and their cultures - Ember, Melvin; Ember, Carol R. (USA : Macmillan, 2001)
The focus of Countries and their cultures is on the countries around the world, what is and what is not commonly shared culturally by the people who live in the country. As the reader will see, some countries have a distinctive national culture.
Vol 2
Includes bibliographical references and index
Keywords: Ethnology- Encyclopedia -- Encyclopedias